PENGEMBANGAN BAHAN AJAR SISTEM PERNAPASAN MELALUI MOODLE YANG BERORIENTASI MENINGKATKAN LITERASI DIGITAL SISWA - Fatoni, Achmad (Perspektif Ilmu Pendidikan, 2022)
Digital literacy is an important skill in the era of industry 4.0 because digital technology is affecting many aspects of life. As an executive institution of the education system, schools have to play a role in the citizens’ digital literacy by implementing a learning programme that is oriented towards the improvement of students digital literacy. To support that affair, this research is aimed to develop a respiratory system teaching material that is oriented to improve students’ digital literacy. The development model used in this research is the ADDIE model that consists of five stages; analyze, design, develop, implement and evaluate. Teaching material was going through feasibility tests on the concept, media, and language aspects by two validators in each aspect. The test and trial process is executed by the students of SMAN 23 Jakarta and two biology teachers. The results of feasibility tests are the following; 3,40 on concept aspect, 3,47 on media aspect and 3,70 on language aspect that indicates a very valid criterion. The trial test results also shown a very valid criterion with the following values; 3,32 on students’ trial test and 3,75 on teachers’ trial test. The overall result of the respiratory systems teaching material is 3,53 which is indicating that the product is very feasible to be used as a learning material in schools and expected to improve students digital literacy